Novel oxidative routes to N-arylpyridoindazolium salts - Levitskiy, Oleg A.; Grishin, Yuri K.; Magdesieva, Tatiana V. (Beilstein Journal of Organic Chemistry, 2024)
A novel facile approach to N-arylpyridoindazolium salts is proposed, based on direct oxidation of the ortho-pyridine substituted diarylamines, either using bis(trifluoroacetoxy)iodobenzene as an oxidant, or electrochemically, via potentiostatic oxidation. Electrochemical synthesis occurs under mild conditions; no chemical reagents are required except electric current. Both approaches can be considered as a late-stage functionalization; easily available ortho-pyridyl-substituted diarylamines are used as the precursors.
Keywords: anodic oxidation; diarylamines; electrochemical cyclization; pyridoindazolium salts; reversible ring closure